Processos juntivos de causa : um estudo dos usos variáveis em textos escritos - Zago, Priscilla Zanforlim [UNESP] (2014)
The goal here is to analyse the variable accomplishment of conjuctive processes of causa in the syntactic, semantic and pragmatic fields (as PAIVA, 1992; NEVES et al. 2008; PAIVA and BRAGA, 2010) and the possible correlation with the Discourse Traditions (as KABATEK, 2003; LONGHIN-THOMAZI, 2011a,b) in written texts by students in the Middle School of a public school in São José do Rio Preto, in the state of São Paulo. From a functional-based junction model (HALLIDAY, 1985; KORTMANN, 1997; RAIBLE, 2001; HOPPER e TRAUGOTT, 2003), we recognize that the casual mastery is realized through different structural combination modes between sentences and/or phrases and introduces semantic and pragmatic polysemy. We also understand that casualty involves logical implication as well as discursive-pragmatic factors, related to social aspects and individual intentions and expectations about the world. Therefore, the main goal of the research is achieved by an analyses of cause constructions consolidation that considers the intersection between the following options: i) tactical axis (parataxis, hypotaxis and subordination); ii) semantic axis (causa and effect, effect and causa, fact and explanation, assertion and explanation, and assertion and conclusion); and iii) pragmatic axis (content, epistemic and speech act – as SWEETSER, 1990). Then we investigate the extent to which discourse tradition, in which texts are used, helps to explain frequency and types os causally scheme found and, in the opposite direction, evaluate the extent to which causal junction schemes help to verge the discourse tradition. The corpus of this study consists of 130 texts of five writers, which were gathered from 2008 to 2011, under the University Extension Project “Development of workshops in reading, interpreting and writing” bound to UNESP, in São José do Rio Preto campus, and coordinated by teachers Luciani Tenani and Sanderléia Longhin. Regarding the ...